Bibliometric Analysis of Nature-Based Solutions Research in Infrastructure and Construction - Aidil Fitriansyah (Jurnal Teknik Sipil, 2026)
Nature-based solutions (NbS) are increasingly promoted as alternatives or complements to conventional grey infrastructure for addressing climate risks, environmental degradation, and rapid urbanization. Despite rapid growth in global NbS scholarship, systematic synthesis of infrastructure- and construction-related applications remains limited. This study presents a bibliometric analysis of 186 journal articles indexed by Google Scholar, published between 2016 and 2025, with an explicit focus on infrastructure contexts. Data were collected using Publish or Perish, screened through predefined criteria, and analyzed using descriptive statistics and VOSviewer science mapping. Results show a marked publication increase after 2019, peaking in 2024 and 2025. Dominant outlets include Sustainability, Water, and Blue-Green Systems. Highly cited works address NbS for urban water management, stormwater control, and coastal flood risk reduction. Keyword co-occurrence analysis identified four thematic clusters: (1) NbS for water and coastal infrastructure, (2) NbS for flood and hydro-meteorological risk, (3) NbS, ecosystem services, and urban green infrastructure, and (4) conceptual frameworks and performance evaluation. Although infrastructure-oriented NbS research is expanding quickly, empirical work on construction management, life cycle performance, and implementation in low- and middle-income countries remains limited. Future research opportunities lie in integrating NbS within project planning and delivery, particularly in rapidly urbanizing settings such as Indonesia.